Ergonomia e design no projeto de espaços de trabalho: o balcão de atendimento dos Correios - Fontes, Andréa Regina Martins (2011)
This research, compiled from the theoretical foundation in the areas of Ergonomics and Design, takes as object of study the social process of designing in a postal company, in which aims at producing knowledge and assisting with new project practices in the context of Ergonomics. The problem focused the linkage between Ergonomics, Project, and Use detailed by a social process of designing that highlight the question of how conflict of values are materialized in technical devices from the variables and its demonstration of use. The evaluation of the results, aims at redeeming the relationships between the actors and conflicts of meaning repercussions on the construction of the artifact. There were highlighted the conflict of values (matters relating the actors and their relationships), conflicts of variables (questions relating to the project options and interfaces of communication within the group) and inadequacies of use (questions relating to the quality of the object from its use) as means of social structure analysis, the spaces of this practice and obstacles to its achievement were accentuated. The role of the coordinator of the social process of project as a negotiator and interfaces employed as means of language were highlighted as well. In conclusion, the results of the social process-centric approach in the context of Ergonomics can approximate project and use, integrating in the public sphere the phases of the Ergonomic Work Analysis and designing activities. Considering this, the results of this process is not the materialization of technical devices as an end, but as resources capable to bring flexibility and significance to the activity of work, seeking to perceive and conceive the object in use manifestation, i.e., in its social function, including the different aspects that form it.